Change in left ventricular diastolic function after pioglitazone treatment in patients with type 2 diabetes mellitus: A protocol for systematic review and meta-analysis. Issue 1 (6th January 2023) - Song, Han; Li, Yunye; Yu, Ruiming; Meng, Xiangbin; Bi, Yanwen
Abstract : Background: Pioglitazone is currently used as an anti-diabetic agent and can reduce cardiovascular events in in patients with type 2 diabetes mellitus (T2DM). Left ventricular diastolic dysfunction has been recognized as an early manifestation of myocardial dysfunction in T2DM patients. This systematic review and meta-analysis aimed to investigate changes in the left ventricular diastolic function after the treatment of pioglitazone. Methods: A systematic literature search of PubMed, Embase, and the Cochrane Library until May 2021 with keywords pioglitazone and left ventricular diastolic function was performed in accordance with the meta-analysis of observational studies in epidemiology guidelines and preferred reporting items for systematic reviews and meta-analyses statement. Three reviewers independently selected the studies and extracted data. Quality assessment of the included studies was undergone. A fixed effects model was used to calculate overall effect sizes. Subgroup analyses were subsequently performed. A fixed effects model was used to calculate the overall effect size. Subgroup analyses were then performed. Results: Seven studies with 233 patients were investigated. We found pioglitazone significantly improved hemoglobin A1c (%) in patients with T2DM and left ventricular diastolic function had an improvement tendency (weighted mean difference [WMD], 0.03; 95% confidence interval [CI], 0.01–0.05, P < .01) despite moderate heterogeneity ( I 2 = 66%). Subsequent subgroup analysis indicated that left ventricular diastolic function were significantly improved (WMD, 0.20; 95% CI, 0.12–0.29, P < .001) in T2DM patients whose average age < 55 after receiving pioglitazone treatment. However, in T2DM patients with mean age ≥ 55 years, there was no significant improvement of left ventricular diastolic function (WMD, 0.02; 95% CI, 0–0.04, P = .04). Conclusion: Pioglitazone treatment significantly improved left ventricular diastolic function in type 2 diabetic patients with a mean age of < 55 years, but did not improve left ventricular diastolic function in patients with a mean age of ≥ 55 years.